Liberation Education in the Surah of the Qur'an Al-'Ankabut 43 - Kiptiyah, Maryatun; Misbah, M.; Rahman, Miftahur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Liberation is a human right, in the Qur'an surah al-Ankabut verse 43, it is explained about freedom of thought. In this case, man is free to express his opinion, which is contained in the theory of Paulo Freire. In this study, the author used Farid Esack's theory of liberation hermeneutics and combined it with the concept of liberation education. Among the keys of esack farid hermeneutics are; taqwa, taqwa, al-mustad'afun, qist and adl and jihad. In this case, the author finds the result in the form of: first, Q.S al-Ankabut verse 43 explains that Allah will give a basis to those who think broadly to express their opinions. Secondly, in this verse, there is a motivation for people who learn to think deeply and freely release the results of their thoughts in the absence of the authority of the teacher over the students.